Management and Outcomes of Facial Nerve Hemangiomas: A Systematic Review of the Literature - Lesha, Emal; Dugan, John E.; Cecia, Arba; Nichols, C Stewart; Orr, Taylor J.; Nezha, Anxhela; Parikh, Kara A.; Khan, Nickalus R. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Objectives To conduct a systematic review of facial nerve hemangiomas (FNH), focusing on patient characteristics, management options, and treatment outcomes.Design A systematic review was performed following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, utilizing PubMed, EMBASE, Scopus, and Cochrane databases from inception to December 31, 2022.Setting Literature sourced from various databases providing information on FNH cases.Participants A total of 176 patients with FNH were included in the study, identified from 40 articles meeting inclusion criteria.Main Outcome Measures Patient demographics, lesion characteristics, preoperative symptoms, surgical approaches, and postoperative outcomes, including House-Brackmann (HB) grades.Results Among the 1,682 initially identified articles, 40 were included in the final review. From these, a total of 176 patients (mean age = 42.7 ± 12.8, 51.1% male) were included for analysis. Bivariate analysis showed that patients with longer preoperative symptom duration and facial nerve sacrifice had significantly greater postoperative HB Grades (p < 0.001). Additionally, a strong positive correlation was observed between pre- and postoperative HB Grades (Spearman's rho = 0.649). Multivariable linear regression analysis showed that both facial nerve sacrifice (β = 0.86, 95% confidence interval [CI]: 0.38–1.34; p < 0.001) and greater preoperative HB Grades (β = 0.36, 95% CI: 0.20–0.53; p < 0.001) were associated with significantly greater postoperative HB Grades, but preoperative symptom duration did not persist as a significant predictor of postoperative HB Grades.Conclusion FNHs are rare lesions of the skull base affecting the temporal bone. Our findings highlight the role of preoperative facial nerve function and intraoperative preservation of the facial nerve in predicting postoperative outcomes. Timely resection of lesions that prioritizes facial nerve preservation is critical to achieving optimal patient outcomes.
Keywords: facial nerve hemangioma; facial nerve; skull base; facial nerve palsy; microsurgery